The Influence Of Product Quality And Price On The Purchase Decision Of Honda Brand Motorcycles At Bintang Motor Lahat Dealer - Hiru Saputra Jaya; Markus Markus; Emilia Sholiha (Jurnal Fokus Manajemen, 2026)
This study aims to determine how Product Quality and Price partially and simultaneously influence the purchasing decision for Honda motorcycles at the Bintang Motor Lahat dealership. The sample size for this study was 38 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS software, resulting in a regression equation . The results showed a significant effect between Product Quality and the purchasing decision for Honda motorcycles at the Bintang Motor Lahat dealership. Price also significantly influenced the purchasing decision for Honda motorcycles at the Bintang Motor Lahat dealership. The F-test showed that Product Quality and Price simultaneously influenced the purchasing decision for Honda motorcycles at the Bintang Motor Lahat dealership.